ANALISIS HUBUNGAN FAKTOR LINGKUNGAN DENGAN KEJADIAN MALARIA DI WILAYAH KERJA PUSKESMAS WONDIBOI - Auri, Zakaria; Fabanyo, Rizqi Alvian; Samaran, Elisabeth (Politeknik Kesehatan Kemenkes Sorong, 2024)
Wondiboi district is one of the areas in Teluk Wondama district which is included in malaria endemic areas. The aim of the research is to analyze the relationship between environmental factors and the incidence of malaria in the Wondiboi Community Health Center. Research Method: Observational research design, with a case control study design approach. A total sample of 112 divided into 56 case groups and 56 control groups. The instrument used was a questionnaire. Data analysis used the Chi-Square test. The research results showed that environmental factors related to the incidence of malaria were the presence of wire mesh in ventilation (p=0.000), the presence of ceilings in the house (p=0.000), the existence of breeding places (p=0.000), the presence of resting places. place (bushes) (p=0.000), and the presence of livestock pens around the house (p=0.000). The conclusion is that there is a relationship between environmental factors and the incidence of malaria in the Wondiboi Community Health Center.